Disrupting Cu trafficking as a potential therapy for cancer - Qasem, Zena; Pavlin, Matic; Ritacco, Ida; Avivi, Matan Y.; Meron, Shelly; Hirsch, Melanie; Shenberger, Yulia; Gevorkyan-Airapetov, Lada; Magistrato, Alessandra; Ruthstein, Sharon (Frontiers in Molecular Biosciences, 2022)
Copper ions play a crucial role in various cellular biological processes. However, these copper ions can also lead to toxicity when their concentration is not controlled by a sophisticated copper-trafficking system. Copper dys-homeostasis has been linked to a variety of diseases, including neurodegeneration and cancer. Therefore, manipulating Cu-trafficking to trigger selective cancer cell death may be a viable strategy with therapeutic benefit. By exploiting combined in silico and experimental strategies, we identified small peptides able to bind Atox1 and metal-binding domains 3-4 of ATP7B proteins. We found that these peptides reduced the proliferation of cancer cells owing to increased cellular copper ions concentration. These outcomes support the idea of harming copper trafficking as an opportunity for devising novel anti-cancer therapies.